Determinasi Ketahanan Pangan di Delapan Negara ASEAN (2012-2022): Pendekatan Data Panel - Maharani, Essa; Marpaung, Grace Natalia (Jurnal Sosial Ekonomi Pertanian, 2025)
Abstract Food itself is one of the crucial issues in development both at the national and global levels because food is the right of every citizen who must be maintained in quality and quantity (Rachman et al., 2021). Food availability that is less than the needs can cause an unstable economy and can disrupt national food security. This study aims to analyze what factors affect the food security of 8 ASEAN member countries. This study uses panel data regression analysis method with Ordinary Least Square (OLS) method which is processed using E-Views software version 12. The results showed that GDP per capita (PPP), rice production, and population have a significant effect on the food security index. On the other hand, the annual average inflation variable does not significantly affect the food security index in 8 ASEAN member countries in 2012-2022. Therefore, the importance of policy implications of ASEAN member countries in maintaining food stocks, distribution systems, price stability, so that the increase in GDP per capita (PPP) is felt evenly and effectively to strengthen the country's food security conditions. Keywords: ASEAN, food security, rice paddy production, ordinary least square, GDP per capita (PPP).